Konsep Perlindungan Istri pada Kekerasan dalam Rumah Tangga (KDRT) Perspektif Hukum Islam: The Concept of Wife Protection in Domestic Violence in Islamic Legal Perspective - Rosmita, Rosmita; Dewi Indriani; Harniah, Harniah (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
This research aims to determine the concept of protecting wives from Domestic Violence (KDRT) from an Islamic legal perspective. Also know about the protection of punishment for the wife who was the victim in this incident. The type of research used in writing this thesis is library research. The data analysis technique used is descriptive analytical using a deductive mindset. The research results show; 1) The Islamic concept of overcoming domestic violence is by determining each husband and wife's respective rights and obligations, then Islam provides direction in reminding each couple if they are negligent in their obligations in a virtuous way. In resolving problems, Islam orders to bring in negotiators from the man's family and the woman's family. 2) According to Islamic law, all parties are responsible for resolving domestic violence problems, starting from the husband as head of the household, then negotiators from both families, then also people in government who are responsible, in this case represented by the religious court.